Analysis of the influence of certain foods on endometriosis control and the positive and negative of drug treatment: a narrative review (Research, Society and Development, 2021)
Objectives: Describe the scientific evidence of the benefits and harms of some foods in controlling endometriosis and analyze the main strengths and weaknesses of hormonal treatment. Methodology: Narrative bibliographic review, with search for publishies in the Pubmed/Medline virtual database using the terms and Descriptors in Health Sciences (DeCS): endometriosis AND nutrition NOT pregnancy and endometriosis AND contraceptives, Hormonal NOT pregnancy in English. Eleven articles that natch the theme were selected. Results: A study showed that the consumption of two portions of beef was associated with a 56% increase in the diagnosis of endometriosis while another study found that the consumption of citrus fruits reduced the risk of having endometriosis by 22%. Regarding pharmacological treatment, dienogest 2 mg was associated with improvement in dysmenorrhea symptoms and preservation of fertility, but its safe use is for a period of less than 65 weeks. Niu et al. (2021) observed that after a period of 12 to 24 months, patients with etonogestrel implant tend to have no pelvic pain, however, the use of this medication evolved with a high removal rate due to its side effects. Conclusion: the treatment of endometriosis has several options and the choice of one of these should be based on the particularity that each woman presents in front of their tolerability and degree of discomfort with each medication and the importance of a multidisciplinary approach in the treatment of endometriosis.